Note on the Optimum Pricing of Annuities - Eytan Sheshinski (Center for Economic Studies and ifo Institute (CESifo), 2003)
In a perfectly competitive market for annuities with full information, the price of annuities is equal to individuals' (discounted) survival probabilities. That is, prices are actuarially fair. In contrast, the pricing implicit in social security systems invariably allows for cross subsidization between different risk groups (males/females). We examine the utilitarian approach to the optimum pricing of annuities and show how the solution depends on the joint distribution of survival probailities and incomes in the population.
Keywords: 330